2018
DOI: 10.20964/2018.02.16
|View full text |Cite
|
Sign up to set email alerts
|

Stray Current Distributing Model in the Subway System: A review and outlook

Abstract: Subway system has been widely applied to the urban rail transit system. However, many negative impacts such as the electrochemical corrosion on the subway track and third-party buried metallic infrastructure caused by the stray current, has gradually appeared. This kind of electrochemical corrosion will cause a great threat on buried metallic structure and personal safety. Numerous scholars studied this from various aspects, in which the stray current model is extensively used as an effective means of analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…The stray current can polarize, either anodically or cathodically, the buried pipelines at the anodic or cathodic zone, respectively. Resulting from the distinguishing environments, the specific reaction equation is diverse, which are oxygen absorption corrosion and hydrogen evolutional corrosion [14,15]. Stray currents are mainly conducted through the soil, and thus their scope of influenc is relatively limited.…”
Section: Introductionmentioning
confidence: 99%
“…The stray current can polarize, either anodically or cathodically, the buried pipelines at the anodic or cathodic zone, respectively. Resulting from the distinguishing environments, the specific reaction equation is diverse, which are oxygen absorption corrosion and hydrogen evolutional corrosion [14,15]. Stray currents are mainly conducted through the soil, and thus their scope of influenc is relatively limited.…”
Section: Introductionmentioning
confidence: 99%
“…The study of these currents is of interest from an engineering point of view, as it results in electrochemical corrosion of metal structures close to the subway system. An updated review of the current distribution models can be found at Wang et al (2018). However, the modeling of stray currents is difficult as all the metallic structures around the railway need to be considered, rail and rail-to-earth resistances can change locally and the grounding system can be more complex than the usually accepted resistor network model.…”
Section: Stray Current Associated To Transportation Systemsmentioning
confidence: 99%
“…Currently, the URT parameters are measured either online or offline [11]- [13]. Wang et al [14] proposed the field test method after analyzing the impacts of track-earth transition resistance, track potential and longitudinal track resistance on the return system. Liu et al [15] put forward an approach to test the track-earth transition resistance under AC power supply, but the test approach faces large errors.…”
Section: Literature Reviewmentioning
confidence: 99%